Analisis Likuiditas dan Efisiensi Operasional Pada Sisa Hasil Usaha (SHU) Koperasi Pegawai Balitbang Kemendikbud: Analysis of Liquidity and Operational Efficiency on the Remaining Business Results (SHU) of the Ministry of Education and Culture's Employee Cooperative - Purwatiningsih, Rosita Tri; Kusuma , Dian Putri Ayu; Anggraini, Ria; Syahla, Farelia Naurah (CV Warnak Johanna Nusantara, 2026)
This study aims to analyze the effect of liquidity and operational efficiency on the Remaining Operating Results (Sisa Hasil Usaha/SHU) of the Balitbang Kemendikbud Employees’ Cooperative during the 2022–2024 period. This research employs a descriptive quantitative approach using secondary data obtained from the cooperative’s financial statements and supervisory reports. Liquidity is examined using the current ratio, while operational efficiency is measured through the operating expense to operating income ratio (BOPO). The results indicate that the cooperative’s liquidity level is relatively positive and supports smooth operational activities. However, excessively high liquidity at the end of the research period indicates the presence of idle funds that have not been optimally utilized. In terms of operational efficiency, the increase in the BOPO ratio in 2024 shows that operating expenses grew faster than operating income, resulting in a decline in SHU. Simultaneously, all variables have an effect on the level of SHU. Therefore, balanced liquidity management and effective control of operating expenses are required to improve the cooperative’s financial performance in a sustainable manner.